Multicell cooperative beamforming scheme based on channel correlation statistics and limited feedback - HE Shi-wen1; HUANG Yong-ming1; YANG Lv-xi1 (Tongxin xuebao)
In order to reduce the amount of information exchange between base stations（BS） and user feedback information required by multicell cooperative beamforming systems,an estimation algorithm of channel vector function was proposed by making jointly use of limited feedback channel parameters and channel spatial correlation matrix.Based on the estimated channel vector functions,a multicell cooperative extended zero-forcing beamforming algorithm was developed.Compared with the existing multicell cooperative algorithms,the proposed scheme achieves a better tradeoff between the feedback/backhaul overhead and the rate performance,which was verified by our numerical simulation results.